Literature Analysis on Improving Science Literacy Through An Inquiry-Based Learning Approach for Students - Sari, Yulia Lelyta; Harianto, Rony; Amilatus, Nuri; Zahra, Nurul Atiyah EM.; Evito, Glenaldo Achmad Zhafran (Islamic Journal of Integrated Science Education (IJISE), 2025)
Scientific literacy is a crucial part of measuring the progress of an educational process. However, to improve scientific literacy skills, it is necessary to understand how scientific literacy can be developed in the learning process. The purpose of this study is to provide an overview of improving students' scientific literacy through an inquiry-based learning approach. Data were collected through library research from various sources, including books, journals, and previous research findings. The results indicate that inquiry-based learning is effective in improving students' scientific literacy. This study demonstrates that inquiry-based learning can help students become more engaged and active in the learning process. It can also improve their critical and analytical thinking skills. This study found that inquiry-based learning methods still provide significant benefits in improving students' scientific literacy, despite several constraints, such as the amount of time required and limited availability of tools. Group learning, the use of lecture techniques, discussions, and technology such as online learning platforms are some of the suggested solutions.